Cuantificación de taninos totales en el extracto hidroalcohólico de las hojas de otholobium pubescens (poir) j. w. grimes “culen”, proveniente de la ciudad de Huamachuco, marzo 2016”. - Salvatierra Paulo, Kelita Madaith (2011)
The study present is a descriptive, retrospective and crosscut type, and it was developed with the purpose of determining the drug interactions presents in prescriptions of patients hospitalized at the Medicine B service of the Trujillo Regional Teaching Hospital – MINSA (H. R. D. T.) from September to October 2010 and there was obtained a total of 480 prescriptions. These prescriptions were evaluated by means of the analytical bibliographical method, is found that 89% (427 prescriptions) presented drug interactions. The characteristics of the patients were determined according to the sex and age of the patients who received that service and it was found that 57% (28 patients) were male and the 20.5% (10 patients) were between the ages 80 and 89 years old. The drug interactions in the prescriptions were identified and quantified and it was found that the most frequent were: Carbonato de Calcio - Sulfato ferroso (14.64%); Omeprazol – Fenitoína (14.29%) and Heparina Clopidogrel (11.43%) and the most frequent drugs in the interactions were: Furosemida, Omeprazol and Ceftriaxona. There were also determined the clinically significant drug interactions and it was found: clinical significance 1, 2 and 3 with 3.22%, 12.54% and 14.26% respectively